O Tráfico de Aves Silvestres em Fortaleza: Implicações Bioéticas e Vivências de Compradores - Batista, Luiza Amélia Oliveira (2010)
This survey developed in Fortaleza - Ceará - Brazil is about the experiences of some people who buy wild birds by means of the illegal trade and the bioethical implications of such practice. The main question is: why do the considered group of people purchase and take wild birds in captivity? The objective of this research is to understand the studied people’s motivation, feeling and perception as owners of wild birds as well as the relationship between them and their birds. The illegal trade is one of the main responsible for the biodiversity reduction in our country as well as hunting and the natural habitats destruction. Some Brazilian institution such as RENCTAS, IBAMA and Polícia Militar are trying to minimise that problem. At the beginning, some data were obtained from the literary, digital and documentary research. Afterwards, questionnaire and interviews were used to have some information about the buyers of wild birds from different areas of the city. The interviews were based on the Forghieri’s (1997) method. 9 According to the initial question, some results could be discussed. The interviewees have wild birds because of two basic reasons. One of them is affection: some people consider wild birds as pets and partners, whose presence could have therapeutic effects. The other is related to the cultural influence on having birds at home, which comes from the countryside. The tradition of listening to the birds’ twitter contributes for it as well. This study is an empirical phenomenological analysis focused on the considered people’s routine. Besides, this research discusses the wild birds traffic according to the Bioethics in the context of science and philosophy.